2019
DOI: 10.17707/agricultforest.65.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Toxicity of the Essential Oils of Lippia Citriodora From Two Different Locations Against Rhyzopertha Dominica and Tribolium Castaneum

Abstract: The lesser grain borer, Rhyzopertha dominica (F.), and the red flour beetle, Tribolium castaneum (Herbst), are among broad-based damaging insect pests of agricultural stored products. Because of several side-effects of conventional chemical insecticides to the human health, non-target organisms, and environment, searching for and introducing healthy, inexpensive, accessible and efficient agents is necessary. In the present study, chemical profiles and fumigant toxicity of the essential oils isolated from L. ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The adults of R. dominica were also susceptible to the fumigation of essential oils extracted from Eucalyptus globulus Labill (24-h LC 50 = 3.529 μL/L), Lavandula stoechas L. (24-h LC 50 = 5.660 μL/L), and Apium graveolens L. (24-h LC 50 = 53.506 μL/L) [ 37 , 38 ]. The fumigation of the essential oils of Lippia citriodora Kunth (24-h LC 50 = 37.349 μL/L), Melissa officinalis L. (24-h LC 50 = 19.418 μL/L), and Teucrium polium L. (24-h LC 50 = 20.749 μL/L) resulted in significant mortality in T. castaneum [ 39 , 40 , 41 ]. The essential oils of Schinus molle L. (48-h LC 50 = 806.50 μL/L) and Artemisia sieberi Besser (24-h LC 50 = 33.80 μL/L) also had notable fumigant toxicity against the adults of T. granarium [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adults of R. dominica were also susceptible to the fumigation of essential oils extracted from Eucalyptus globulus Labill (24-h LC 50 = 3.529 μL/L), Lavandula stoechas L. (24-h LC 50 = 5.660 μL/L), and Apium graveolens L. (24-h LC 50 = 53.506 μL/L) [ 37 , 38 ]. The fumigation of the essential oils of Lippia citriodora Kunth (24-h LC 50 = 37.349 μL/L), Melissa officinalis L. (24-h LC 50 = 19.418 μL/L), and Teucrium polium L. (24-h LC 50 = 20.749 μL/L) resulted in significant mortality in T. castaneum [ 39 , 40 , 41 ]. The essential oils of Schinus molle L. (48-h LC 50 = 806.50 μL/L) and Artemisia sieberi Besser (24-h LC 50 = 33.80 μL/L) also had notable fumigant toxicity against the adults of T. granarium [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fumigant toxicity of some plant-derived essential oils against O. surinamensis, R. dominica, T. castaneum and T. granarium has been documented in previous studies; it was found that the essential oils of Agastache foeniculum (Pursh) Kuntze, Achillea filipendulina Lam., and Achillea millefolium L. with respective 24-h LC 50 values of 18.781, 12.121, and 17.977 µL/L, had high toxicity on the adults of O. surinamensis [31,[34][35][36]. The adults of R. dominica were also susceptible to the fumigation of essential oils extracted from Eucalyptus globulus Labill (24-h LC 50 [39][40][41]. The essential oils of Schinus molle L. (48-h LC 50 = 806.50 µL/L) and Artemisia sieberi Besser (24-h LC 50 = 33.80 µL/L) also had notable fumigant toxicity against the adults of T. granarium [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows that the most abundant chemotypes are αand β-citral (51.35 ± 0.08% and 23.86 ± 0.04%, respectively), followed by geraniol (6.16 ± 0.01%) and geranyl acetate (5.95 ± 0.02%). It should be remarked that the number of identified compounds and their relative abundance greatly depend on the EO extraction conditions, storage conditions, harvest periods and geographical origin, being limonene, citral, caryophyllene, neral and/or geranial the most commonly found (Elechosa et al, 2017;Farahmandfar, Asnaashari, Pourshayegan, Maghsoudi, & Moniri, 2018;Ishkeh, Asghari, Shirzad, Alirezalu, & Ghasemi, 2019;Kizil et al, 2018;Ebadollahi and Razmjou, 2019;Krzyśko-Łupicka, Sokół, & Piekarska-Stachowiak, 2020).…”
Section: Chemical Analysis Of Lemon Verbena Essential Oilmentioning
confidence: 99%